DAMPAK STRATEGIC POSITIONING PADA KEPUTUSAN PEMBELIAN: OPTIMALISASI KUALITAS ATAU KOMPROMI BIAYA DI ERA DIGITAL? - Ghina Saumalia; Melina Vaniatan; Naqiyyah Auryn Syahla Maladi; Deta Trinalti Oktavia (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Strategic positioning is the determination of a company's position in the market to influence consumer purchasing decisions, either through optimizing product quality or compromising costs. This study aims to explore the impact of strategic positioning on consumer purchasing decisions in the digital era, focusing on the role of innovation, digital technology, and understanding consumer needs as key factors in achieving competitive advantage. The results of the study indicate that the right positioning strategy, such as emphasizing product quality or comparison with competitors, can shape positive consumer perceptions. However, excessive cost leadership strategies can damage brand image if not managed properly. This study provides insight for companies to balance quality and price in designing an effective positioning strategy.